2003
DOI: 10.2135/cropsci2003.1852
|View full text |Cite
|
Sign up to set email alerts
|

RAPD Variations in Selected and Unselected Blue Grama Populations

Abstract: used for reclamation and ground cover (Hitchcock, 1950). These adaptive features have stimulated some interest Blue grama (Bouteloua gracilis H.B.K. Lag. ex Steud.) is one of in utilization and cultivar development of this species the most widespread native grasses in western North America. Little (Smith and Phan, 1999). Two blue grama populations, is known about the genetic diversity of this species and the genetic one a balanced multi-site composite (BMSC) and the shift in selected populations. Random amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
3
12
1
Order By: Relevance
“…In addition, the finding of high within-accession genetic variation (91%; Table 2) implies that the seed collection from a single site may provide an adequate genetic diversity for creating an improved germplasm used for nearby site reclamation. This differs from the previous recommendation of using multi-site composite materials to maintain high levels of genetic diversity at new restoration sites [53].…”
Section: Discussioncontrasting
confidence: 79%
“…In addition, the finding of high within-accession genetic variation (91%; Table 2) implies that the seed collection from a single site may provide an adequate genetic diversity for creating an improved germplasm used for nearby site reclamation. This differs from the previous recommendation of using multi-site composite materials to maintain high levels of genetic diversity at new restoration sites [53].…”
Section: Discussioncontrasting
confidence: 79%
“…Although the number of polymorphic loci is relatively low for the AFLP method, our results are consistent with other B. gracilis studies, including one resulting in 167 polymorphic loci and an average of 28 bands per primer combination(Fu, Ferdinandez, Phan, Coulman, & Richards, 2003) and one RAPD study that resulted in 69 polymorphic loci with an average of only six bands per primer combination(Phan, Fu, & Smith, 2004). All cultivar varieties strongly cluster with natural populations 1B, 1C, 3B, and 9B.…”
supporting
confidence: 89%
“…As -Santacruz et al, 2004;Phan et al, 2004). While these studies demonstrated higher variation among individuals within populations (88% and 98%, respectively), both studies covered relatively small sample areas, and used different primer combinations, which may account for the higher within-population variation observed in these studies.…”
Section: Genetic Variation and Structure In B Gracilismentioning
confidence: 90%
See 1 more Smart Citation
“…The mean band frequency for each population ranged from 0.12 to 0.74 with an average of 0.43 (Table 2). The mean band frequency was higher as compared with Phan et al, (2003).…”
Section: Discussionmentioning
confidence: 76%